Mainstreaming Low-Cost Hydroponics Using Fermented Plant Juice for Sustainable Lettuce Production in Urban Farming - Quirante, Zandra Anciano; Politud, Eric Randy R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the viability of a low-cost hydroponic system for food security in the Zamboanga Peninsula, employing a mixed-methods approach. The research assessed the acceptability, growth performance, and economic feasibility of hydroponic lettuce production using locally sourced organic inputs, specifically Fermented Plant Juice (FPJ). Hydroponics is seen as beneficial for addressing space limitations and improving food security in the region, though adoption is hindered by limited technical knowledge, material access, and capital. Estrosa and Olmetie lettuce varieties showed optimal performance.  Nitrate levels in Estrosa and Green Wave were undetectable, and while Olmetie and Invicta absorbed more nitrate with FPJ, all levels remained within international safety limits. Cadmium was not detected. Recommendations for the Zamboanga Peninsula include agricultural modernization through technical training, start-up assistance, material accessibility, and R&D support. Public awareness campaigns for low-cost hydroponics using FPJ, crop diversification, farmer engagement, and urban/peri-urban adoption incentives are also suggested. Growers are advised to prioritize Estrosa and Green Wave for lower nitrate uptake and ensure correct FPJ preparation.